Analysis of the Implementation of Purchasing Information System Based on Enterprise Resource Planning (ERP) Using Microsoft Dynamics Nav Application (Case Study of PT. Simpang Kanan Lestarindo) - Ilhamzah Pahutar; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
Enterprise Resource Planning (ERP) is a vital component in improving company performance in today's digital era. PT Simpang Kanan Lestarindo implements an ERP-based purchasing information system using the Microsoft Dynamics NAV application to optimize the purchasing management process. Microsoft Dynamics NAV offers various features that support purchasing management, including purchase requests, purchase orders, goods receipt, purchase invoices, and payments. This research aims to analyze the effectiveness of the implementation of this information system in improving the efficiency and accuracy of the purchasing process in the company. The research method used is qualitative with a case study approach, which involves collecting data through interviews and observations. The results showed that the implementation of Microsoft Dynamics NAV has had a positive impact on the company's performance, despite some challenges in the system adaptation process. This research is expected to contribute to the development of science and become a reference for further research in the field of information systems and purchasing management.